2012
DOI: 10.1182/blood-2012-08-449744
|View full text |Cite
|
Sign up to set email alerts
|

IGHV-unmutated and IGHV-mutated chronic lymphocytic leukemia cells produce activation-induced deaminase protein with a full range of biologic functions

Abstract: IntroductionChronic lymphocytic leukemia (CLL) follows either an indolent or an aggressive course 1 and clinical decompensation is often accompanied by the appearance of new or increasing numbers of genetic aberrations associated with shorter survival, "clonal evolution." 2 The mechanism(s) responsible for the generation of these genetic abnormalities are not defined in CLL, which is not the case in certain other human cancers, especially lymphoid malignancies of germinal center (GC) origin, in which activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 51 publications
7
82
1
2
Order By: Relevance
“…18 PKCa-KR cells also exhibited an elevated proliferative capacity compared with control B cells, both in vitro and in vivo ( Figure 3D,E). Supporting this, aicda expression, which has been associated with increased CLL cell proliferation, 19,20 was significantly increased in GFP + CD19 + cells expressing PKCa-KR at the later stages of culture compared to MIEV-expressing cells ( Figure 3F). We previously demonstrated that PKCa-KR-transduced cells exhibited reduced PKC activity during the early stages of the OP9 co-culture, as expected ( Figure 4A, left).…”
Section: Pkca-kr Transduced Cells Exhibit Features Of the Poor Prognomentioning
confidence: 55%
See 1 more Smart Citation
“…18 PKCa-KR cells also exhibited an elevated proliferative capacity compared with control B cells, both in vitro and in vivo ( Figure 3D,E). Supporting this, aicda expression, which has been associated with increased CLL cell proliferation, 19,20 was significantly increased in GFP + CD19 + cells expressing PKCa-KR at the later stages of culture compared to MIEV-expressing cells ( Figure 3F). We previously demonstrated that PKCa-KR-transduced cells exhibited reduced PKC activity during the early stages of the OP9 co-culture, as expected ( Figure 4A, left).…”
Section: Pkca-kr Transduced Cells Exhibit Features Of the Poor Prognomentioning
confidence: 55%
“…48 Indeed, up-regulation of activationinduced deaminase has been associated with elevated double-strand DNA breaks in CLL cells, promoting the generation of genetic aberrations. 20 Therapies that reduce proliferation do, therefore, offer an important treatment option for progressive CLL. Our findings support the development of clinical studies with ruboxistaurin and sotrastaurin in CLL, given the recent promising data assessing the clinical efficacy of BCR-targeting inhibitors such as the Btk inhibitor ibrutinib.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, this was thought to indicate functional inactivation of AID or defects in other yet unidentified factors critical for SHM. However, more recently, AID was shown to be expressed in both M-CLL and U-CLL at both the mRNA and protein level, and more particularly within the small proportion of cells that are undergoing or have recently undergone division (22). AID was capable of inducing SHM and CSR after in vitro stimulation with CD40 and IL4, a system, in essence, mimicking costimulatory signals provided by T cells in vivo.…”
Section: Ig Gene Repertoirementioning
confidence: 99%
“…AID was capable of inducing SHM and CSR after in vitro stimulation with CD40 and IL4, a system, in essence, mimicking costimulatory signals provided by T cells in vivo. On these grounds, it was proposed that the lack of SHM in U-CLL clones in vivo is not due to an intrinsic AID defect, but rather due to active inhibition (22).…”
Section: Ig Gene Repertoirementioning
confidence: 99%
“…4,5). Activation-induced cytidine deaminase (AID), which is normally required for both SHM and CSR, is expressed in a small proliferative compartment within the CLL clone, irrespective of the immunoglobulin heavy variable (IGHV) gene mutational status, and can be functionally induced in vitro under conditions that mimic T-cell help (6). Furthermore, ongoing CSR and high AID expression define a subgroup of U-CLL displaying even worse prognosis, underscoring the importance of intense (micro) environmental stimulation for shaping clonal behavior and eventual clinical outcome (7).…”
Section: Introductionmentioning
confidence: 99%